Interdisciplinary Approach in Engineering Education - Zeidmane, Anda; Cernajeva, Sarmite (International Journal of Engineering Pedagogy, 2011)
The analysis of the scientific literature available on the types of general competences and their classification caused the authors to conclude that it is necessary to implement interdisciplinary approach in engineering education to develop competences necessary for engineers to make them competitive in the labour market. The attention should be paid to a professional foreign language, computer literacy and educational psychology recommendations. To improve professional foreign language skills, CLIL (Content and Language Integrated Learning) method should be integrated in the study process of engineering education. In order to develop information literacy competence, it is important to create a single e-study environment. The academic staff, developing study subjects for engineering programmes, should focus on the study content and study methods. As regards the content, the compromise should be sought between fundamental acquisition of the knowledge of the subject matter, the know-how of the application of this knowledge as well as the use of brand new software in the calculations. The paper presents the examples of the application of the interdisciplinary approach in the universities, where the authors of the paper are affiliated: the LUA (Latvia University of Agriculture) and the RTU (Riga Technical University), respectively.